Knowledge and attitude of dental trauma among dental students in Saudi Arabia - Al-Shamiri, Hashem Motahir (Eur J Dent, 2015)
OBJECTIVE: The aim of this study was to assess the level of knowledge and attitude of Saudi dental students in the management of dental trauma in children. MATERIALS AND METHODS: A self-administered questionnaire comprising 17 close-ended questions was used in this survey. The questions were divided into three parts including: Personal and professional profile; knowledge assessment; attitude toward dental trauma. Data of 307 respondents were analyzed using SPSS (Statistical Package for Social Studies) version 22.0 (IBM Corporation, Chicago, IL, USA). RESULTS: The response rate was 76.8%. Around 40.3% of students reported attending additional courses about dental trauma with a significant difference between males (57.2%) and females (19.4%). The vast majority of students (95.7%) stressed the importance of dental trauma education. While 77% could correctly identify the media of transportation of an avulsed tooth, only 26.9% of the students knew the proper method of transportation. Regarding the knowledge of immediate replantation, only 67.5% of students responded correctly. CONCLUSION: The present study demonstrates an insufficient knowledge concerning dental trauma management among dental students in Saudi Arabia. This highlights the need to improve the knowledge of dental students regarding dental trauma and its management using a variety of educational methods such as problem-based learning and powering the curriculum concerning those topics of dental trauma.